Implementasi Metode Yanbu’a untuk Meningkatkan Kemampuan Siswa Membaca dan Menghafal Al-Qur’an - Syarifah Syarifah; Farida Isroani; Nurul Azizah; Jaziela Huwaida; Nishfi Nurin Nada (Fitrah: Journal of Islamic Education, 2022)
This study aims to analyze the implementation of the Yanbu’a method to improve the ability to read and memorize the Qur'an. This study focuses on three problems, namely implementation, constraints, and learning outcomes. This study examines the use of the Yanbu’a method at SMP Techno Insan Kamil Tuban, East Java. This study uses a qualitative research method with a narrative study approach. Obtaining data using observation techniques, interviews, and documentation studies. The data sources consist of research informants which include teachers and students, and the literature which includes documents of student learning achievements, and books and journals as a theoretical basis. The results of the study revealed that this method utilizes tiered volumes from volume one to volume seven, and is studied in two ways, namely classical visualization and classical volume, and by combining two hours of weekly instruction. The obstacles encountered in applying this method are differences in student abilities, lack of parental support, difficulty for teachers to understand and convey the material of gharib volume six. Student learning outcomes respond well to this method, and it is proven that 85% of students are able to read the Al-Qur'an as well as write and memorize it.